Prenatal and pubertal testosterone exposure imprint permanent modifications in the prostate that predispose to the development of lesions in old Mongolian gerbils - Biancardi, Manoel F.; Perez, Ana P.S.; Caires, Cássia R.S. [UNESP]; Falleiros, Luiz R. [UNESP]; Góes, Rejane M. [UNESP]; Vilamaior, Patrícia S.L. [UNESP]; Freitas, Diógenes R.; Santos, Fernanda C.A.; Taboga, Sebastião R. [UNESP] (Wolters Kluwer, 2017)
The prostate is an accessory sex gland that develops under precise androgenic control. It is known that hormonal imbalance may disrupt its development predisposing this gland to develop diseases during aging. Although the hypothesis regarding earlier origins of prostate diseases was proposed many years ago, the mechanisms underlying this complex phenomenon are poorly understood. Therefore, the aim of this study was to evaluate the prostates of old male gerbils exposed to testosterone during intrauterine and postnatal life using morphological, biometrical, stereological, Kariometric, immunohistochemical, and immunofluorescence analyses. Our findings demonstrate that prenatal and pubertal exposure to testosterone increases the susceptibility to the development of prostate diseases during aging. The presence of a more proliferative gland associated with foci of adenomatous hyperplasia in animals exposed to testosterone during the prenatal and pubertal phase show that the utero life and the pubertal period are important phases for prostatic morphophysiology establishment, which is a determinant for the health of the gland during aging. Therefore, these findings reinforce the idea that prostate disease may result from hormonal disruptions in early events during prostate development, which imprint permanently on the gland predisposing it to develop lesions in later stages of life.
Keywords: Adenomatous hyperplasia; Endocrine-disrupting chemicals; Gerbil; Prostate development; Testosterone